Women’s Rebellion to Find Voices in Enola Holmes - Aulia Anggraini; Pratiwi Retnaningdya (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
Directed by Harry Bradbeer, Enola Holmes (2020) portrays a 16-year-old girl who searches for her mother who disappeared while fighting for women’s rights to vote. In this movie, Victorian women are bound by a law that forbids them from having the right to vote. This article aims to identify and describe women’s rebellion in their struggle for voices in the Victorian era. Employing Bartlett's rebellious feminism within a feminist perspective of John Stuart Mill, the article analyses how Eudoria Holmes, a female character, undergoes dangerous ways in attempt to fight for women's rights to vote. Using the script and cinematographical elements, the film analysis reveals that Eudoria Holmes rebels against the values of Victorian society on three levels: individual, familial, and societal. Becoming an independent and courageous mother, she plants the seeds of rebellion to her daughter, Enola Holmes. Moreover, Eudoria also establishes a secretive women’s circle to build solidarity with the purposes of social and political activism in the form of women's suffrage campaigns.